Fucoxanthin inhibits the proliferation of MOLM13 cells by targeting AKT to disrupt glucose metabolism - Niu, Tingting; Chen, Ying; Sun, Mengmeng; Shi, Cong; Zou, Duobing; Wu, Wei; Chen, Yuzhan; Chen, Juanjuan; Chen, Haimin; Ouyang, Guifang; Mu, Qitian (Frontiers in Pharmacology, 2025)
Fucoxanthin is a natural carotenoid that has remarkable anti-tumor effects and an excellent safety profile. Here, we combined molecular docking, dynamics simulations, and functional assays (CCK-8, flow cytometry, glucose/ATP detection) to decipher the mechanism of Fucoxanthin on FLT3-ITD AML cells. Fucoxanthin (25 μM) reduced MOLM13 (FLT3-ITD) cell viability by 63.6% (P < 0.01), inducing G0/G1 arrest via CDK4 downregulation and apoptosis through Bcl2 suppression. Fucoxanthin also inhibited the glucose uptake, GLUT1 membrane translocation, and ATP production. Mechanistically, fucoxanthin directly bound to AKT and inhibited its kinase activity by 57.9%, while AKT overexpression rescued the glucose/ATP suppression (P < 0.05). Molecular dynamics revealed critical interactions between fucoxanthin and Phe-236/Lys-179. These results suggest that fucoxanthin may selectively target AKT-dependent glucose metabolism in MOLM13 cells, warranting further investigation into its role in addressing metabolic alterations in FLT3-ITD AML.